Effects of moving-vehicle wakes on pollutant dispersion inside a highway road tunnel. (November 2016) - Bhautmage, Utkarsh; Gokhale, Sharad
Abstract: This study investigates the pollutant dispersion in a highway road tunnel in the presence of moving-vehicle wakes by a relative-velocity approach using 3-D CFD (3-Dimensional Computational Fluid Dynamics). The turbulent behavior of airflow around different-shaped vehicles and its impact on the pollutant dispersion have been studied. The different-shaped vehicle geometries were extracted, and simplified and dimensioned basing the typical vehicles on Indian roads. The model has been verified with the literature data of static pressure around a moving vehicle body before applying to simulate concentrations, and validated with on-site data at two locations. The results showed that wakes varied with the size, shape and speed of vehicles. The mixed-traffic flow produced higher near-field wakes and accelerated the piston effect, pushing pollutants toward the tunnel roof and out of exit portal in short-time. The findings have particular significance in the studies related to dispersion inside the tunnels having a mixed traffic of different dimensions and shape. Highlights: Moving-vehicle produces near-field wakes, and accelerates piston effects. Piston effect is significant even in a highly-trafficked short tunnel. Moving-vehicle wakes considerably alter the pollutant levels along the tunnel. Relative airflow over a vehicle body is crucial to the mixing of pollutants. Abstract : This study investigates the effects of moving-vehicle wakes on pollutant dispersion inside a road tunnel to determine the suitability of a ventilation system for healthy air quality.